PENGARUH REKOMENDASI AUDIT KINERJA TERHADAP CAPAIAN INDIKATOR KINERJA UTAMA (IKU) PADA KEMENTERIAN PERIKANAN KABUPATEN MUNA - Shally Amalia Nur’aini; Mulyati Akib (Tamilis Synex: Multidimensional Collaboration, 2025)
This study aims to analyze the effect of performance audit recommendations on the achievement of Key Performance Indicators (KPI) in government agencies. Performance audit is one of the monitoring mechanisms that plays a role in providing strategic feedback for agencies in improving the efficiency, effectiveness, and accountability of program implementation. KPI achievement is a benchmark for the success of implementing organizational tasks and functions in a measurable manner. This study uses a quantitative approach with a simple linear regression method, and data is collected through questionnaires and documentation at agencies that have received audit recommendations for at least two consecutive years. The results of the study indicate that performance audit recommendations have a positive and significant effect on KPI achievement, with a regression coefficient value of 0.893 and a significance value of 0.000 (<0.05). The coefficient of determination (R²) value of 0.664 indicates that 66.4% of the variation in KPI achievement can be explained by the implementation of audit recommendations. Thus, the better the follow-up to audit recommendations, the higher the KPI achievement of government agencies. This study emphasizes the importance of performance audits as an evaluation tool as well as a driver of improving the performance of public sector agencies. Audit recommendations that are carried out consistently contribute significantly to the achievement of organizational performance targets.